AN EFFECT OF BIODIESEL (B20) ON LIFE TIME LOCOMOTIVE FUEL FILTER - Maruf, Muhammad; Haryono, Ihwan (BPPT, 2019)
The effect of using B20 palm oil biodiesel on rail locomotive fuel filters was evaluated in this study. The generator water separator filter, generator main filter and locomotive drive filter after being used along the filter replacement period were analyzed in laboratories and compared with new ones as reference. The analysis was using SEM/EDS, FTIR and GC. The FTIR and GC test results show that the fuel filter has a number of deposits from the components of biodiesel fuel, that are diesel and biodiesel. However, morphological test results using SEM show that the filter surface has not been completely covered by liquid and fuel deposits. The results of the tests and analysis indicated that the usage of 125 hours (for locomotive genset) and 3 months for locomotive drive engine with 20% palm biodiesel fuel can still guarantee the filtration to maintain the performance and prevent damage to fuel and engine system components.